Implementasi Design Thinking pada Perancangan Animasi sebagai Upaya Edukasi Kesehatan Indera Pendengar: Upaya Pencegahan Noise Induced Hearing Loss (NIHL) pada Generasi Muda Menggunakan Media Animasi 2D - Ardiyanti, Afifah Nur; Kurniawan, Rendya Adi; Muslihah, Isnawati; Rachman, Anung (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2025)
Personal listening devices such as earphones and headphones have become digital products that help the younger generation maintain their productivity or simply serve as tools for them to enjoy audio more privately. Unfortunately, excessive use of these devices will trigger a hearing impairment known as Noise Induced Hearing Loss (NIHL). The design of this educational media in the form of 2D animation is carried out to educate the general public, especially teenagers to young adults who use personal listening devices, and to contribute to reducing the number of NIHL sufferers due to these devices. The research method was conducted using a qualitative approach with a design thinking method to understand the issues related to the use of the device from the user's perspective, so that the solutions will be more relevant to the needs of the target audience. The design of 2D animations with a minimalist illustration style and storytelling base relevant to the target audience's habits can capture their attention, ensuring that the auditory health education within it is conveyed accurately.